2002
DOI: 10.1145/566171.566192
|View full text |Cite
|
Sign up to set email alerts
|

Projected state machine coverage for software testing

Abstract: Our research deals with test generation for software based on finite state machine (FSM) models of the program specification. We describe a set of coverage criteria and testing constraints for use in the automatic generation of test suites. We also describe the algorithms used to generate test suites based on these coverage criteria, and the implementation of these algorithms as an extension of the Murφ model checker[4]. The coverage criteria are simple but powerful in that they generate test suites of high qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The commonly recommended test objectives are similar to (1) transition coverage for EFSMs which provides the worst fault detection effectiveness albeit with the fewest coverage tasks, and (2) transition-pair coverage which provides better fault detection effectiveness than transition coverage, but worse than BZ-TT. Furthermore, we also observed that the expressive power of the notations used to specify the test objectives was not adequate to Hartman et al [6] Murph/ User defined projections on states and transitions No describe our intentions thus providing arguments for a better fault modeling notation for software testing.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The commonly recommended test objectives are similar to (1) transition coverage for EFSMs which provides the worst fault detection effectiveness albeit with the fewest coverage tasks, and (2) transition-pair coverage which provides better fault detection effectiveness than transition coverage, but worse than BZ-TT. Furthermore, we also observed that the expressive power of the notations used to specify the test objectives was not adequate to Hartman et al [6] Murph/ User defined projections on states and transitions No describe our intentions thus providing arguments for a better fault modeling notation for software testing.…”
Section: Introductionmentioning
confidence: 92%
“…We use an adapted version of the simplified bounded buffer example from [6]. Producers can deposit items in a bounded buffer with a given capacity (2 in this example), and Consumers can withdraw items from the bounded buffer.…”
Section: Model-based Test Generation Techniquesmentioning
confidence: 99%
See 3 more Smart Citations